PEMILIHAN FRAMEWORK APLIKASI WEB BERBASIS JAVA MENGGUNAKAN ANALYTICAL HIERARCHY PROCESS (AHP) - Azhari, Lukman (Jurnal Informatika, 2018)
Currently, many web application frameworks that available in the internet, we know from wikipedia that more than 20 java frameworks for developing web application. Frameworks is a developed base of related design or related architecture. A framework provides a set of libraries or classes that used by us to developing a web application, they will cooperate each others to accomplish certain tasks in the intended domain [SCHWABE 2001]. Decision makers can choose application frameworks that can be implemented in information system development. In this research writer will examine features in framework Java server faces, Struts, and Spring MVC with using ISO 9126 for getting criteria in choosing framework. This research will compare hierarchically with approaching Analytical Hierarchy Process (AHP). Finally, from the result of this research we got the best alternatif from Java framework. The best java framework is Java Framework Spring MVC in comparison of Java Framework Java Server Faces and Java Framework Struts. So, it is very clear that Java Framework Spring MVC is the best framework which supported in developing information system.